Job stress of university employees: The role of guidance and counseling - Purnama, Diana Septi; Rachmawati, Indriyana; Kurniasari, Mitta; Millenia, Putri; Rahmadania, Alyoriek; Dewanti, Septinda Rima (ProGCouns: Journal of Professionals in Guidance and Counseling, 2024)
Work stress appears as an interesting topic in the era of society 5.0, this condition can even arise among university workers. The emergence of work stress among workers in higher education can be caused by involvement in work. This lack of involvement triggers low performance and low welfare. The aim of this research is to obtain a representation of the work stress of university employees in Yogyakarta and the factors that influence it. The research sample was 329 workers at Yogyakarta City Universities who were selected using proportional random sampling techniques. Limitations for determining the research sample using the Krejcie Table for sample size. The data collection technique uses the Job Stress Scale adopted from Vic Catano's Stressors and Stress Outcomes, consisting of 8 aspects, namely competence, workload, work schedule, role conflict, role ambiguity, routine, rewards, life balance, and policy making. The data analysis technique used in this research is descriptive. The research results showed that 72% of workers said they were not experiencing work stress in terms of workload, routine, rewards and life balance. Meanwhile, health factors show a high percentage compared to the environment, meaning that health describes the work stress experienced by workers. University guidance and counseling service units can at least play a role in providing the training, counseling and therapy programs needed to overcome work stress.